Further evidence for links between facial width‐to‐height ratio and fighting success: Commentary on Zilioli et al. (2014). Issue 4 (18th September 2014) - Třebický, Vít; Fialová, Jitka; Kleisner, Karel; Roberts, S. Craig; Little, Anthony C.; Havlíček, Jan
Abstract : Recent research has reported an association between facial width‐to‐height ratio (fWHR) and both fighting performance and judgments of formidability in a sample of mixed martial arts (MMA) combatants. The results provide evidence of fWHR being associated with sporting performance and aggression in men. However, it has been argued that the effect of fWHR might be a by‐product of associations between body size and behavioral measures. Here we tested whether fWHR is associated with perceived aggressiveness, fighting ability and success in physical confrontation, while controlling for body size, also in a sample of MMA fighters. We found that perceived fighting ability was predicted by weight but not by fWHR. In contrast, both fWHR and body weight independently predicted perceived aggressiveness. Furthermore, we found positive associations between fWHR and fighting performance which appear to be independent of body size. Our findings provide further support for the proposal that fWHR is associated with fighting ability and perceived aggression, and that these effects are independent of body size. Therefore, fWHR might be considered as a viable and reliable marker for inference of success in male intra‐sexual competition. Aggr. Behav. 41:331–334, 2015. © 2014 Wiley Periodicals, Inc.